Сравнительно-анатомические данные об артериальном русле почек позвоночных - Бурачинский, М.Т. (Вестник зоологии, 1970)
The kidney arteries were investigated in representatives of classes of fish, amphibia, birds and mammals. It is observed that in phylogenesis the extraorganic arteries of kidneys concentrate and intraorganic ones — differentiate correspondignly to the changes in the internal structure of the given organs. The numeric arteries are distributed in fish kidneys according to the simple plan; the glomerula are arranged irregularly, In kidneys of amphibia there are still less arteries, but they are distributed comparatively simply, however the glomerula are grouped near the abdomen surface of the organs. To each kidney of the bird three artery come, the branches of which and glomerula arrange correspondingly to the lobular structure of the organ. The latter is observed even better in mammals, in which two or one artery come to each kidney.